2015
DOI: 10.5604/00306657.1147029
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ghrelin, leptin and pro-inflammatory cytokines after therapy in Obstructive Sleep Apnea Syndrome (OSAS) patients.

Abstract: Elevated leptin levels are not determined by obesity alone, since they decreased with Apnea Hypopnea Index reduction. Higher pro-inflammatory cytokine basal levels observed in patients with OSAS were not correlated with BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 26 publications
(28 reference statements)
1
49
2
2
Order By: Relevance
“…Importantly, a strong correlation between AHI changes and serum cytokine levels has been demonstrated independently of BMI [10]. Another study provided evidence connecting a distinct biomarker pro le, including high IL-6 levels after sleep, in patients with moderate/severe OSAS than those with mild/no OSAS [21].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Importantly, a strong correlation between AHI changes and serum cytokine levels has been demonstrated independently of BMI [10]. Another study provided evidence connecting a distinct biomarker pro le, including high IL-6 levels after sleep, in patients with moderate/severe OSAS than those with mild/no OSAS [21].…”
Section: Discussionmentioning
confidence: 90%
“…The ndings of the current study agree with the study by Kong et al [47] documented that CPAP treatment does not consistently reduce elevated IL-6 levels. However, this issue has been challenged in research, by studies reported that IL-6 level changes were markedly attenuated by long-term CPAP therapy [10,32] or sleep apnea surgical procedures [48]. The pooling of eight published reports in adults with OSAS revealed that plasma IL-6 levels ranged from 1.2 to 131.7 pg/mL before CPAP treatment and signi cantly decreased to between 0.45 to 66.04 pg/mL after CPAP treatment [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, we are among the first to describe patients with abnormally elevated leptin levels in the absence of obesity or a known additional diagnosis. A comprehensive literature search showed that among non-obese patients, differences in leptin levels have been shown with multiple other endocrine conditions (decreased in hypothyroidism 55 and elevated in precocious puberty 56,57 , hyperinsulinemia 57 , elevation of thyroid autoantibodies 58 , idiopathic intracranial hypertension 59 , and hypothalamic dysfunction 60 ), pulmonary conditions (decreased in smokers 32,61 and elevated in asthmatics 62 , adults with impaired lung function 63 , obesity hypoventilation syndrome 64 , and obstructive sleep apnea 65 ), and multiple myeloma 66 and in the setting of elevated uric acid 67 . Despite this extensive list, the magnitude of difference in leptin levels between cases and unaffected controls in these studies was usually only a few nanograms per milliliter, far smaller than the variations we have presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed a reduction in leptin levels with PAP therapy after 1-6 months. [80][81][82] It looks like this effect, especially in the long term, is mediated through BMI reduction. Chin et al found that PAP therapy reduced the visceral fat in patients with OSA with or without changes in body weight.…”
Section: Ghrelinmentioning
confidence: 99%